مصادر ضغوط العمل لدى أخصائي التعلم بالمدارس الحكومية بولاية السيب Work pressure sources for the learning resources specialist at public schools in the state of Seeb - Al Musawii, Abdul Mutalib Sharaf Ali; Al-Hidabi, Dawood Abdulmalek Yahya; Tunku Ahmad, Tunku Badariah; Makkivi, Mohamed El Tahir Osman (International Organization Center of Academic Research, 2019)
This quantitative study discusses the sources of work stress for the learning resources specialist in public schools at "wilayat Seeb". The problem is the increase in the volume of tasks and burdens of the learning resources specialist in the Sultanate's schools, which means increasing "work pressure". Therefore, the study aims at: Diagnosing the sources of work stress in the specialist learning resources in public schools. The researcher adopted the descriptive analytical approach, the study population consisted of (94) individuals, the sample was limited to (55) individuals. The questionnaire consists of (68) statements distributed in (7) axes sources of work pressure. The study findings: The learning resources specialist suffers from sources of great work pressures resulting from the nature of work and change, qualification and training, and the presence of four sources of work stresses are available on average. The results also showed that the source of work-related stress at work is low.